Structural Studies of ZnO Nanostructures and Nano Powders - Nirmala*, B.; Banumathi*, T.V.; Najeema, M.; Kayalvizhi, M. (Asian Journal of Chemistry, 2013)
Nanostructures and nano sized particles have diverted considerable attention among researchers due to their unique properties. Researchers have shown interest in zinc oxide as it may be used as a low cost replacement for Si and GaN. Zinc oxide is one of the most promising semiconducting material due to its piezo electric and transparent conducting properties. It has high electrical conductivity and optical transmittance in the visible region and a good absorption in the UV region. Therefore it can be used as window and sunscreen materials. The nanostructured ZnO has normal applications in sensors, transducers, biomedical devices, optoelectronic devices, solar cells etc. The oxidation of high purity zinc at high temperatures in a muffle furnace yields nanostructures on the surface of metallic zinc. ZnO particles are synthesized using high energy ball-milling technique. The structure and morphology of ZnO nano structures is analyzed using X-ray diffraction method and scanning electron microscope. This paper focuses on the structure and morphology of the furnace melt ZnO nano particles.